The American Sign Language handshape dictionary - Tennant, Richard A.; Brown, Marianne Gluszak (Washington, D.C. : Clerc Books, Gallaudet University Press, 1998)
"The unique feature of this dictionary is that it is organized by handshape rather than by alphabetical order. An American Sign Language learner can look up an unfamiliar sign by looking for the handshape rather than by looking up the word in an alphabetical English glossary. At the same time, an English speaker can look up a sign for a specific word by looking at the Index of English Glossaries located at the end of the dictionary. The introduction includes a history of sign language in the United States. Detailed instructions explain the organization of the handshape sections and the ordering of signs. The illustrations are clear and are described in terms of configuration, location, movement, orientation, and nonmanual markers".--"Outstanding Reference Sources : the 1952 Selection of New Titles", American Libraries, May 1952. Comp. by the Reference Sources Committee, RUSA, ALA.
Includes index.
Also available as an electronic book via the World Wide Web to institutions affiliated with netLibrary, Inc.
Keywords: American Sign Language -- Dictionaries